FAA421 : Principles of animation / Faculty of Film, Theatre and Animation - UiTM, Faculty of Film, Theatre and Animation (Universiti Teknologi MARA (UiTM), 2018)
Students are exposed to the production of 2D animation which introduces to the process including development techniques and management of animation projects from pre-production, production and post production. In enhancing the animated cartoon, this course emphasizes on the importance of the principles of animation through various tools such as flipbook and digital animation to help students to develop further understanding of 2D animation concepts